Long-term Effects of Statins, Blood Pressure-Lowering, and Both on Erectile Function in Persons at Intermediate Risk for Cardiovascular Disease: A Substudy of the Heart Outcomes Prevention Evaluation-3 (HOPE-3) Randomized Controlled Trial - Joseph, P.; Lonn, E.; Bosch, J.; Lopez, P.; Zhu, J.; Keltai, M.; Dans, A.; Reid, Christopher; Khunti, K.; Toff, W.; Piegas, L.; Kim, J.; et al. (Elsevier Inc., 2018)
© 2017 Canadian Cardiovascular Society Background It is unclear whether modifying cholesterol, blood pressure, or both affect erectile dysfunction. Also, there are concerns that erectile dysfunction is worsened by common medications used to treat these risk factors. In this study, we evaluated the effect of: (1) cholesterol-lowering with a statin; (2) pharmacologic blood pressure reduction; and (3) their combination, on erectile function. Methods A priori, this was a secondary analysis of the Heart Outcomes Prevention Evaluation-3 (HOPE-3) randomized controlled trial. Men were 55 years of age or older with at least 1 cardiovascular risk factor. Erectile function was measured using the erectile function domain of the International Index of Erectile Function (IIEF-EF) score. Men with incomplete scores, or who did not engage in sexual activity, were excluded. Using a 2 × 2 factorial design, participants were randomized to rosuvastatin (10 mg/d) or placebo, and to candesartan with hydrochlorothiazide (HCTZ; 16 mg/12.5 mg/d; Cand+HCTZ) or placebo. Primary outcome was change in IIEF-EF from baseline to end of study follow-up. Results Two thousand one hundred fifty-three men were included; mean age was 61.5 years, and mean follow-up was 5.8 years. Mean IIEF-EF score at baseline was 23.0 (SD 5.6). Least square mean change in the IIEF-EF score did not differ with rosuvastatin compared with placebo (-1.4; standard error [SE], 0.3 vs -1.5; SE, 0.3; P = 0.74), Cand+HCTZ compared with placebo (-1.6; SE, 0.3 vs -1.3; SE, 0.3; P = 0.10), or combination therapy compared with double placebo (P = 0.35). Conclusions Cholesterol-lowering using a statin, and blood pressure-lowering using Cand+HCTZ, either alone or in combination, do not improve or adversely affect erectile function.